(untitled) (Journal of the College of Education for Women, 2019)
AbstractDisturbs the social system in any society specially in Iraq other thanother Islamic and Arabic countries. That is according to the abnormalconditions that Iraq has past through as wars and blockage, and lastly theinvasion. Therefore it has been necessary to put this phenomenon understudy and analysis to discover Juvenile Delinquency is one of the mostprominent social phenomenon that the important reasons behind it, and tryingto treat what can be treated of the effects of it upon society.This study is mainly concerned with the explaining the social factorsleading toward juvenile delinquency trying to crystallize the problem of thestudy in the following question: (What are the psychological, social,economical factors leading toward juvenile delinquency?)The study aims at recognizing the order of the different factors ofjuvenile delinquency and knowing the effect of the social factors on it, inaddition to the family factors affecting the delinquency.The importance of the study comes from the importance of thephenomenon itself. The study identifies the social factors resulting in thedelinquency of the juvenile. It is important, for it shows the main family factorsin all its different sides resulting in the behaviour of the juvenile. The studytries to put the scales to treat the phenomenon.In its theoretical frame, the study has discussed the phenomenon ofjuvenile delinquency and the factors behind it.The researcher has showed several former studies in the same fieldthat have focused on the most important factors affecting the appearance ofthe phenomenon.